Pengaruh pemberian probiotik Lactobacillus helveticus Rosell-52 dan Lactobacillus rhamnosus Rosell-11 terhadap kadar limfosit lanjut usia - Wahyuningsih, Retno; SS, Darmono; Margawati, Ani (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2014)
Background: Infectious disease remains a health problem for the elderly. The elderly are susceptible to infection,because the body's ability to fight infection decreases immunity. The immune status can be improved through the effortsof immunization, and nutrition. However the elderly are not sufficient to meet the nutritional needs of food, so probioticcould support nutritional adequacy.Objective: Analyze the effect of probiotic Lactobacillus helveticus Rosell-52 and Lactobacillus rhamnosus Rosell-11 onlevels of lymphocytes in the elderly in Tresna Elderly Social Institution Puspakarma Mataram, West Nusa Tenggara.Methods: This was quasi-experimental study, randomized pre-post control group design. The population is elderly aged60-75 years, involving 45 subjects were divided randomly into two groups, namely the treatment groups givenprobiotics and the control group was given a placebo. Probiotics were given for 4 weeks, with the provision of onecapsule a day. Immunity status in this study was lymphocytes. Data examined included the intake of nutrients (protein,vitamin A, vitamin C, vitamin E, Fe, Zn), health status, quality of sleep, and levels of lymphocytes in the elderly. Datawere analyzed using bivariate with different test Independent sample t-test, Mann-Whitney U test, Spearman, Pearson,and Paired t-test.Results: Increasing number of lymphocytes were significantly in the treatment group (χ ± SD: 1.84 ± 1.85) and in thecontrol group (0.95 ± 5.0). There is no relationship between intake (protein, vitamin A, vitamin C, vitamin E, Fe, Zink),physical health status, and quality of sleep with levels of lymphocytes.Conclusion: Probiotics in 4 weeks is proven to increase the number of lymphocytes in the elderly.